Synergy between Parents and Schools in Strengthening the Integration of Religious Values in Students' Daily Life at YMIK Joglo Junior High School - Nursobah, Asep; A’raaf, Sarah Nofis; Rosyidah, Siti; Hasanah, Uswatun (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The implementation of the Independent Curriculum in Islamic Religious Education (PAI) at YMIK Junior High School aims to strengthen the integration of religious values in students' daily lives. This study analyzes the methods applied to create relevant and contextual learning experiences. Through innovative learning approaches, such as group discussions, community-based projects, and the use of technology, students are invited to understand and apply Islamic values, such as honesty, tolerance, and social care. Extracurricular activities, such as recitation and social services, also play a role in instilling character and ethics based on religious teachings. In addition, collaboration with parents is an important factor in supporting this educational process. The results of the study show that the implementation of the Independent Curriculum at YMIK Junior High School not only improves students' religious understanding, but also develops positive attitudes and social skills that are useful in daily life. This study recommends sustainable strategies to improve the effectiveness of PAI teaching in other schools.